THE INFLUENCE OF EXPLICIT READING STRATEGY INSTRUCTION (ERSI), CONVENTIONAL TEACHING AND READING INTEREST ON THE ELEVENTH GRADE STUDENTS’ READING ACHIEVEMENT AT PGRI 1 OF VOCATIONAL HIGH SCHOOL OF PALEMBANG - Baginda Simaibang; Inderawati Inderawati; Eva Rahma Sari (ELTE Journal (English Languange Teaching and Education), 2017)
This thesis is concerned with The Influence of  Explicit Reading Strategy Instruction (ERSI), Conventional  Teaching and Reading Interest  on The Eleventh Grade Students’ Reading Achievement at PGRI 1of  Vocational High Schoolof Palembang  . The problem of the study is to investigate the influence of explicit strategy instruction, conventional  teaching and students’ reading interest towards  reading  achievement. The total number of populations were 195 students. The sample for this study were 30 students taken through two stage random sampling technique . Data were collected by adopting questionnaire for reading interest and test for ERSI  and reading  achievement. Data were analyzed by using t-test and factorial design (two way anova). Findings show that there are interaction effects  of explicit reading strategy instruction (ERSI), conventional  teaching and students’ reading interest towards  reading  achievement. Conclusion suggests that ERSI  and reading interest have significant roles to improve reading achievement.Keywords: Explicit Reading Strategy Instruction (ERSI), Conventional Teaching, Reading Interest, Reading Achievement.